Programmable quantum circuits in a large-scale photonic waveguide array - Yang Yang; Robert J. Chapman; Akram Youssry; Ben Haylock; Francesco Lenzini; Mirko Lobino; Alberto Peruzzo (npj Quantum Information)
Abstract Over the past decade, integrated quantum photonic technologies have shown great potential as a platform for studying quantum phenomena and realizing large-scale quantum information processing. Recently, there have been proposals for utilizing waveguide lattices to implement quantum gates, providing a more compact and robust solution compared to discrete implementation with directional couplers and phase shifters. We report on the first demonstration of precise control of single photon states on an 11-dimensional continuously-coupled programmable waveguide array. Through electro-optical control, the array is subdivided into decoupled subcircuits and the degree of on-chip quantum interference can be tuned with a maximum visibility of 0.962 ± 0.013. Furthermore, we show simultaneous control of two subcircuits on a single device. Our results demonstrate the potential of using this technology as a building block for quantum information processing applications.